Spatial and temporal variations of net ecosystem productivity in Xinjiang Autonomous Region, China based on remote sensing - Lu, Xiangjun; Chen, Yang; Sun, Yuyin; Xu, Yongming; Xin, Yan; Mo, Yaping (Frontiers in Plant Science, 2023)
Net ecosystem productivity (NEP), which plays a key role in carbon cycle, is an important indicator of the ecosystem carbon budget. In this paper, remote sensing and climate re-analysis data were coupled to estimate the NEP over Xinjiang Autonomous Region, China from 2001 to 2020 based on the modified Carnegie Ames Stanford Approach (CASA) model and the soil heterotrophic respiration model. The spatio-temporal variations of NEP in Xinjiang were analyzed. The annual mean NEP of the study area was high in the east and low in the west, high in the north and low in the south. The 20-year mean vegetation NEP of the study area is 128.54 gC·m-2, indicating that the study area is a carbon sink on the whole. From 2001 to 2020, the annual mean vegetation NEP ranged between 93.12 and 158.05 gC·m-2, and exhibited an increasing trend in general. 71.46% of the vegetation area showed increasing trends of NEP. NEP exhibited a positive relationship with precipitation and a negative relationship with air temperature, and the correlation with air temperature was more significant. The study of the temporal and spatial dynamics of NEP in Xinjiang Autonomous Region can provide a valuable reference for assessing regional carbon sequestration capacity.